Cartoons and the new anti-Semitism : a thesis presented in fulfilment of the requirements for the degree of Master of Design at Massey University, College of Creative Arts, Wellington, New Zealand - Smith, Steven W (Massey University, 2012)
This thesis examines how the use of the Star of David symbol in cartoons published in the three months following the May 31, 2010 Gaza flotilla incident reflects a global new anti-Semitism. The objective is to identify and examine how particular signifiers in editorial-style cartoons are used to communicate an anti-Semitic message. Over the three-month period immediately following the flotilla incident the mechanical and automatic retrieval method, Google Alerts captured cartoons published internationally on the Internet each day. Roland Barthes’ theory of systematic semiotic analysis was employed to examine visual aspects of cartoons for signs which connoted anti- Semitic messages against a framework of criteria drawn from a synthesis of recognised definitions of anti-Semitism. The research supports claims that a new anti-Semitism has spread into the consciousness of mainstream culture. The research suggests that criticism of Israel via the medium of cartoons can cross the line from legitimate criticism to established anti-Semitic manifestations.
Keywords: Antisemitism in the press; Jews; Jewish people; Israel; Caricatures and cartoons